Constructed wetland systems vegetated with different plants applied to the treatment of tannery wastewater - Calheiros, Cristina S.C. (2010)
Wastewaters from leather processing are very complex and lead to water pollution if discharged untreated, especially due to its high organic loading. In this study the survival of different plant species in subsurface horizontal flow constructed wetlands receiving tannery wastewater was investigated. Five pilot units were vegetated with Canna indica, Typha latifolia, Phragmites australis, Stenotaphrum secundatum and Iris pseudacorus, and a sixth unit was left as an unvegetated control. The treatment performance of the systems under two different hydraulic loading rates, 3 and 6 cmd1, was assessed. COD was reduced by 41–73% for an inlet organic loading varying between 332 and 1602 kg ha1 d1 and BOD5 was reduced by 41–58% for an inlet organic loading varying between 218 and 780 kg ha 1 d1. Nutrient removal occurred to lower extents. Phragmites australis and Typha latifolia were the only plants that were able to establish successfully. Despite the high removal of organic content from the influent wastewater, during 17 months of operation, no significant differences in performance were observed between units.